A Systematic Review and Meta-Analysis of Baduanjin Qigong for Health Benefits: Randomized Controlled Trials. (7th March 2017) - Zou, Liye; Sasaki, Jeffer Eidi; Wang, Huiru; Xiao, Zhongjun; Fang, Qun; Zhang, Mark
Abstract : Objective . To investigate the effects of practicing Baduanjin Qigong on different health outcomes. Methods . Six electronic databases were used for literature search through entering the following key words: Baduanjin Qigong, quality of life, sleep quality, and health-related outcomes. Results . Nineteen randomized controlled trials were used for meta-analysis. The aggregated results from this systematic review have shown significant benefits in favour of Baduanjin Qigong on quality of life (SMD, −0.75; 95% CI −1.26 to −0.24; P = 0.004 ), sleep quality (SMD, −0.55; 95% CI −0.97 to −0.12; P = 0.01 ), balance (SMD, −0.94; 95% CI −1.59 to 0.30; P = 0.004 ), handgrip strength (SMD, - 0.69; 95% CI −1.2 to −0.19; P = 0.007 ), trunk flexibility (SMD, −0.66; 95% CI −1.13 to −0.19; P = 0.006 ), systolic (SMD, −0.60; 95% CI −0.94 to −0.27; P = 0.0004 ) and diastolic blood pressure (SMD, −0.46; 95% CI −0.73 to −0.20; P = 0.0005 ), and resting heart rate (SMD, −0.87; 95% CI −1.47 to −0.27; P = 0.005 ). The aggregated results of meta-analyses examining the effect of Baduanjin Qigong on leg power, cardiopulmonary endurance, and pulmonary function remain unclear because of a small number of studies. Conclusions . The aggregated results from this systematic review show that Baduanjin Qigong practice is beneficial for quality of life, sleep quality, balance, handgrip strength, trunk flexibility, systolic and diastolic blood pressure, and resting heart rate. Further studies are necessary to confirm the effects of Baduanjin Qigong on leg power, cardiopulmonary endurance, and pulmonary function (e.g., vital capacity), while considering a long-term follow-up. Registration Number . This trial is registered with International Prospective Register of Systematic Reviews (PROSPERO): CRD42016036966 .